Repurposing metformin for cardioprotection: mechanisms and therapeutic potential across cardiovascular pathologies - Khinchin, Julia; Rakoubian, Ani; Romano, Valentina; Ryan, Thomas; Yarbro, Johnathan; Kobayashi, Satoru; Liang, Qiangrong (Frontiers in Pharmacology, 2026)
Metformin, a cornerstone therapy for type 2 diabetes mellitus, has emerged as a promising cardioprotective agent with effects that extend well beyond glycemic control. This review synthesizes current evidence on the molecular and cellular mechanisms underlying metformin’s glycemic control and cardiovascular benefits, highlighting both AMPK-dependent and AMPK-independent pathways. We examine its modulation of mitochondrial function, oxidative stress, inflammation, autophagy, and apoptosis across major cardiac conditions, including ischemia/reperfusion injury, heart failure, diabetic cardiomyopathy, and anthracycline-induced cardiotoxicity. By integrating evidence from both preclinical and clinical studies, we evaluate the translational potential of metformin’s pleiotropic actions across specific cardiac pathologies and outline key directions for future research and therapeutic innovation. Together, these insights highlight metformin’s promise in reshaping cardiovascular care beyond its traditional role in diabetes management.